2020
DOI: 10.1097/shk.0000000000001585
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-to-Lymphocyte Ratio and Outcomes in Louisiana COVID-19 Patients

Abstract: Background:Due to the rapidly escalating number of cases and the low baseline of overall health in Louisiana, we sought to determine the prognostic value of the neutrophil-to-lymphocyte ratio (NLR) in hospitalized COVID patients in 2 major metropolitan areas with the highest prevalence of casesand exceedingly high rates of obesity and other comorbid conditions.We hypothesized that elevated NLR would be a prognostic indicator of mortality. Methods: This was a review of a prospective registry of adult (18+ years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
126
5
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(160 citation statements)
references
References 24 publications
3
126
5
4
Order By: Relevance
“…To date, six retrospective clinical studies examining the potential use of NLR as a prognostic marker for severe Covid-19 have been published; none in Mexican patients until now [ 22 , 23 , 24 , 25 , 26 , 27 ]. All these clinical studies consistently conclude that NLR is an independent risk factor of mortality in critically ill patients with Covid-19.…”
Section: Discussionmentioning
confidence: 99%
“…To date, six retrospective clinical studies examining the potential use of NLR as a prognostic marker for severe Covid-19 have been published; none in Mexican patients until now [ 22 , 23 , 24 , 25 , 26 , 27 ]. All these clinical studies consistently conclude that NLR is an independent risk factor of mortality in critically ill patients with Covid-19.…”
Section: Discussionmentioning
confidence: 99%
“…The remaining 42 studies were further scrutinized by reading the full text. Finally, only 19 studies were included in this meta-analysis, of which 9 reported the predictive value on disease severity [26][27][28][29][30][31][32][33][34], 6 reported the predictive value on mortality [35][36][37][38][39][40], and 4 reported the predictive value on both disease severity and mortality [41][42][43][44].…”
Section: Selection and Characteristics Of Studiesmentioning
confidence: 99%
“…Neutrophil to Lymphocyte ratio (NLR) has been explored as a prognostic marker for COVID-19, with high level of NLR associated with severity of the disease 43,44 or with higher mortality rates 45,46 . More specific subsets of the Lymphocytes, especially the CD4 + and CD8 + T-cell counts are found to be depleted in severe COVID-19 patients 17,47 .…”
Section: Relationship With Immune Cellsmentioning
confidence: 99%